Analisis Potensi Daerah di Wilayah Eks-Karesidenan Madura Menggunakan Metode Location Quotient dan Shift Share - P, Irma Widianti K (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2020)
he purpose of this study is to find out which sectors are included in the bases and non bases in each regency in the Madura Ex-Residency area through the Location Quotient Analysis (LQ) and Shift Share tools. From the results of the LQ analysis in Madura’s Ex-Residency there are 5 base sectors in Bangkalan Regency, 4 base sectors in Sampang Regency, 8 base sectors in Pamekasan Regency, and 3 Base Sectors in Sumenep Regency. In the Shift Share analysis results in each district consisting of 17 sectors can be determined sectors that inhibit / encouraging, has fast / slow growth, and has fast growth and has a locational advantage when compared to the same sector in other regions.